2016
DOI: 10.1007/s40618-016-0503-z
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of the indication for radioiodine thyroid ablation in differentiated thyroid cancer patients

Abstract: Radioactive iodine therapy is administered to patients with differentiated thyroid cancer (DTC) for eradication of thyroid remnant after total thyroidectomy or, in patients with metastatic disease, for curative or palliative treatment. In past years, thyroid remnant ablation was indicated in almost every patient with a diagnosis of DTC. Nowadays, careful revision of patients' outcome has introduced the concept of risk-based selection of patients candidate to thyroid remnant ablation. The present review aims to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 75 publications
1
5
0
2
Order By: Relevance
“…[15] However, the unavailability of the number and dimension of lymph node metastases were an important limitation of this study. [16] Recent studies reported that increasing number of lymph node metastases and macroscopic lymph node metastases were associated with decreasing overall survival, [17,18] these finding are in agreement with our results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[15] However, the unavailability of the number and dimension of lymph node metastases were an important limitation of this study. [16] Recent studies reported that increasing number of lymph node metastases and macroscopic lymph node metastases were associated with decreasing overall survival, [17,18] these finding are in agreement with our results.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, aend tail whole body scan ( WBS) can be done after postoperative RAI; the results of this scan may identify previously undiagnosed disease, and may change the initial staging and facilitate early recurrence detection that is based on serum thyroglobulin (Tg) measurement and/or WBS. [6,7] Although I-131 is widely used, RAI therapy is not without adverse consequences. RAI can impact quality of life due to side effects such as acute or chronic xerostomia, acute or chronic sialoadentitis, and dental caries.…”
Section: Introductionmentioning
confidence: 99%
“…• In low-risk DTC patients, there is little evidence to suggest that thyroid ablation may improve the very low risk of disease-specific mortality and to have an effect on the low rate of recurrence [31][32][33]. Besides, it is not demonstrated that delayed diagnosis and treatment of persistent disease may decrease the chance of cure.…”
Section: Narrative Of the Recommendationmentioning
confidence: 99%
“…Для эффективной аблации остаточной тиреоидной ткани вводились активности 131 I от 1,1-2,8 ГБк (30-75 мКи) при Т 1a,b N 0 M 0 и T 2 N 0 M 0 ; эффективная РЙТ местнораспространенных форм ДРЩЖ достигалась при введении 3,7-5,5 ГБк (100-150 мКи) 131 Неоднозначной является и оценка эффективности аблации. Критерием эффективной радиойодаблации, по мнению большинства зарубежных авторов [61][62][63][64][65][66][67], является отсутствие очагов накопления радиойода в проекции ложа щитовидной железы и патологического включения 131 I при проведении диагностической сцинтиграфии всего тела с радиойодом через 6-12 мес.…”
Section: ядерная медицинаunclassified